Effectiveness Of Self Instructional Leaflet On Knowledge And Attitude Regarding Prevention And Management Of Varicose Veins Among Housekeeping Workers Employed At Panimalar Medical College Hospital & Research Institute. - Savithri Kanganda Bopaiah; Kavin Mozhi James; Mythili Krishnan; Florence Nightingale K A; Pappu B; Thenmozhi; Keerthika Vengatesan (Revista Electronica de Veterinaria, 2024)
Background: Varicose veins, a common condition involving the dilation and twisting of veins, often affect the lower limbs and can lead to discomfort, pain, and complications such as ulcers. This condition arises due to prolonged standing, heavy lifting, and other physical strain, making it particularly prevalent amonghousekeeping workers in hospitals. These workers, tasked with maintaining cleanliness and sanitation, often engage in repetitive tasks that put significant pressure on their venous system. Due to the nature of their work, they are frequently at risk of developing varicose veins. This study was conducted to assess the ffectiveness Of Self Instructional Leaflet On Knowledge And Attitude Regarding Prevention And Management Of Varicose Veins Among Housekeeping Workers Employed At selected hospital ChennaiMethods: Using a convenient sampling technique, a descriptive cross-sectional study was conducted among 60 housekeeping workers employed at private hospitals in Chennai. A semi-structured knowledge questionnaire and an attitude Likert scale were administered to gather data. The results were tabulated and interpreted.Results: Among the 60 respondents, the pre-test revealed that the majority, 59 (98.4%), had inadequate knowledge. After the intervention, the post-test showed a significant improvement, with 38 (63.4%) demonstrating adequate knowledge. In terms of attitude, the pre-test showed that 29 (48.3%) of the participants had a poor attitude, while the post-test revealed that 27 (45%) had an excellent attitude. There was a significant increase in the mean knowledge score from 8.91 to 14.43, with a mean difference of 6.43. The standard deviation increased from 9.02 to 14.22, and the t-value of 24.41 was found to be highly significant at the 5% level. Regarding the attitude, the mean score increased from 10.4 to 12.2, with a mean difference of 1.8. The standard deviation rose from 80.1 to 93.9, and the t-value of 13.4 was also highly significant at the 5% level.The post-test level of knowledge and attitude, when analyzed with selected demographic variables, showed that knowledge was significantly associated with factors such as age, gender, and years of experience (p< 0.0001), but not with other demographic variables. However, the level of attitude did not show any significant association with any of the demographic variables.A positive correlation was observed between knowledge and attitude.Conclusion: Varicose veins cannot be completely cured, and even after surgical removal, recurrences are common. Individuals who develop venous ulcers experience the highest levels of morbidity and a significantly reduced quality of life. Unlike the deep venous system, clots in superficial veins rarely embolize, making the risk of pulmonary embolism low. However, improving knowledge about the prevention and management of varicose veins is essential. With better awareness, individuals can take proactive steps to prevent varicose veins, reducing their occurrence both in hospitals and the community, ultimately enhancing overall quality of life.